1934
DOI: 10.1128/jb.27.3.303-324.1934
|View full text |Cite
|
Sign up to set email alerts
|

The Physiological Youth of a Bacterial Culture as Evidenced by Cell Metabolism

Abstract: In an earlier contribution from this laboratory (Walker and Winslow, 1932) it was shown that toward the end of the initial lag period in either peptone or lactose-peptone water, there is manifest an enormous increase in metabolic activity, particularly with respect to anmnonia production. Formation of CO2 per cell per hour is increased thirty to seventy fold and formation of NH3 nitrogen fifty to one-hundred-and-fifty fold as compared with the peak stability rates. There is, in these increases, a very clear de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1937
1937
1963
1963

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…The extension of the phase of adjustment at any one temperature, due to an increase in the age of the inoculum, has been noted by other workers (Muller, 1895;Penfold, 1914). A possible explanation for this result can be found in the work of Martin (1932), Walker et al (1934, and Huntington and Winslow (1937). Huntington and Winslow (1937) showed that the metabolic activity of the bacterial cell decreases after it enters the exponential phase of growth.…”
mentioning
confidence: 58%
“…The extension of the phase of adjustment at any one temperature, due to an increase in the age of the inoculum, has been noted by other workers (Muller, 1895;Penfold, 1914). A possible explanation for this result can be found in the work of Martin (1932), Walker et al (1934, and Huntington and Winslow (1937). Huntington and Winslow (1937) showed that the metabolic activity of the bacterial cell decreases after it enters the exponential phase of growth.…”
mentioning
confidence: 58%
“…The fermenting capacity is surprisingly uniform. The very short but very greatly increased rate of metabolism observed by Bayne-Jones and Rhees (1929) and by Walker, Winslow, Huntington and Mooney (1934) was not evident. These authors observed that cells just coming out of lag, before the plate count showed a doubling of the cells, had a rate of metabolism 4 to 8 times as high as a few hours later, during the logarithmic phase.…”
Section: Age Of Cellsmentioning
confidence: 75%
“…They point out however that while maximal rates were accountable on the basis of increased cell size, decreased cell size could not account for the decreased metabolic rates during the stable growth phases. Huntington and Winslow (1934) were unable to explain increased rates of carbon dioxide production entirely on the basis of cell size. They concluded that this increased cell size was a factor to be considered in conjunction with increased metabolism in defining physiological youth, but that it did not serve as a means of elucidation.…”
Section: Discussionmentioning
confidence: 98%
“…Increases in the rates of metabolism have been noted by Bayne-Jones and Rhees (1929), Martin (1932), Walker and Winslow (1932) and others. Walker, Winslow, Huntington and Mooney (1934) calculated that increased rates of heat production, oxygen consumption, carbon dioxide production, and ammonia-nitrogen production were explainable for the most part on the basis of increased cell size. They point out however that while maximal rates were accountable on the basis of increased cell size, decreased cell size could not account for the decreased metabolic rates during the stable growth phases.…”
Section: Discussionmentioning
confidence: 99%